A Brief Introduction to ULOI and RIMAPS Technique - Favret, Eduardo Alfredo (2013)
I was really surprised when this prestigious Journal of Powder Metallurgy and Mining invited me to be part of the Editorial Board, because I am mostly a physicist characterizing metallic and biological surfaces using different optical and electronic microscopes and during the last years I focus my research interest on biomimetism (self-cleaning surfaces). As you can see there is nothing about powder metallurgy and mining. However, it is my profound believe that science need to be interdisciplinary and scientists opened-mind. Specialization is fine but sometimes avoids you understanding new facts. I hope that the journal?s interest goes in the same way. Let me introduce you one of my research activities: the application of two surface characterization techniques, ULOI and RIMAPS, for the study of topographical patterns.